Legal Politics in Regional Oil and Gas Governance: Toward Sustainable Regulation - Dicky Eko Prasetio; Ridwan Arma Subagyo; Oky Sapto Mugi Saputro; Bazarova Dildora Baxadirovna (Indonesian Journal of Administrative Law and Local Government, 2025)
Oil and gas exploration and exploitation in Bojonegoro Regency actually creates problems in the form of the absence of statutory regulations that accommodate legal developments and community needs. This research aims to formulate a political, legal and policy orientation so that oil and gas exploration and exploitation in Bojonegoro Regency can provide optimal benefits for the community and is in line with sustainable development. This research is socio-legal or interdisciplinary legal research which examines legal aspects normatively accompanied by analysis based on policy theory. The research results show that the legal implications of the absence of updates to statutory regulations relating to oil and gas exploration and exploitation in Bojonegoro Regency are that philosophically, sociologically and juridically they lack legitimacy and tend to be difficult to implement due to the complexity of the community's legal needs, especially after the passing of the Ciptaker Law. Legal politics related to oil and gas exploration and exploitation in Bojonegoro Regency, namely the need for legal products that are responsive, ecological and progressive in character so that they can be implemented through various policies that are able to make oil and gas exploration and exploitation in Bojonegoro Regency a success as well as the need for revisions to Regional Regulations and Regent Regulations so that in line with the substance of the Ciptaker Law and adapted to actual legal needs in the Bojonegoro community. Keywords: Exploration; Exploitation; Policy; Oil and Gas; Legal Politics.